Дитячий «цвинтар» ХІ—ХІІ ст. на Подолі - Козак, О.Д. (Археологія і давня історія України, 2019)
Вводяться до наукового обігу результати палеопатологічного дослідження комплексу дитячих поховань давньоруського часу, відкритих на території Поштової площі у м. Києві. Проаналізовано захворювання та соціальний стан похованих дітей. In the cities of the Middle Ages children was the
most sensitive group of people who responded to starvation,
infection and social stress with high mortality
rate and increased morbidity.
7 children’s burials (one belongs to twins of 6—
9 month), located relatively compact on the outskirts of
the lower city, were investigated in this project. Most
children died at the age between 1 month and 3 years
old. They have vestiges of metabolic disorders (scurvy,
rickets and anemia) and infectious diseases (tuberculosis,
nonspecific meningitis) on the bones. In one case,
differential diagnosis was performed between congenital
syphilis and rickets. Both diseases rarely happened
in ancient Kiev. The pathological profile virtually repeats the pattern
of morbidity in adolescents and young women buried in the marginal cemeteries of Podil. Regarding, studied
complex can be considered a children’s quarter on the territory of some burial ground of the period.
On the other hand, the similarity of the symptoms in most children, as well as two children (possibly twins)
in one coffin indicates that at least part of them could die during one of the epidemics that took place in Kiev
during the 11th—12th centuries which were obviously the most active on Podil.